2021
DOI: 10.1021/acs.jpca.1c03225
|View full text |Cite
|
Sign up to set email alerts
|

3-Phonon Scattering Pathways for Vibrational Energy Transfer in Crystalline RDX

Abstract: A long-held belief is that shock energy induces initiation of an energetic material through an energy up-pumping mechanism involving phonon scattering through doorway modes. In this paper, a Fermi's golden rule-based 3-phonon theoretical analysis of energy up-pumping in RDX is presented that considers possible doorway pathways through which energy transfer occurs. On average, modes with frequencies up to 102 cm −1 scatter quickly and transfer over 99% of the vibrational energy to other lowfrequency modes up to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 72 publications
2
16
0
Order By: Relevance
“…Within the time resolution of our experiment, we do not see a significant pump dependence to the earliest transient spectra, though it is possible that pump-dependent VET dynamics occur on time scales faster than we can resolve. 31 Prompt VET was also reported by Shi et al 10 for RDX microcrystals, where 2D IR cross-peaks were evident at dynamical times as early as 0.1 ps. Such rapid appearance of transient spectra, along with the reported 0.48 ps coherence dephasing time constant, 10 strongly suggests that the initial excitation of modes across the spectrum is due to a coherent VET process.…”
Section: B Time-dependent Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Within the time resolution of our experiment, we do not see a significant pump dependence to the earliest transient spectra, though it is possible that pump-dependent VET dynamics occur on time scales faster than we can resolve. 31 Prompt VET was also reported by Shi et al 10 for RDX microcrystals, where 2D IR cross-peaks were evident at dynamical times as early as 0.1 ps. Such rapid appearance of transient spectra, along with the reported 0.48 ps coherence dephasing time constant, 10 strongly suggests that the initial excitation of modes across the spectrum is due to a coherent VET process.…”
Section: B Time-dependent Resultssupporting
confidence: 66%
“…Recent theoretical treatments by Chung and co-workers 28−31 indicate that RDX is a highly anharmonic molecular crystal where excited, intramolecular vibrational modes rapidly scatter into low-frequency lattice modes. 31 Indeed, several experimental and theoretical studies (refs 32−34 for examples) have indicated anisotropic shock response in RDX, wherein it is hypothesized that select lattice distortions both couple strongly to high-frequency, "intramolecular" vibrations and cause increased heating due to irreversible mechanical deformation on preferential slip planes. 33,35,36 To the best of our knowledge, there have been only two previous time-resolved, experimental studies of vibrational dynamics in solid RDX.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low-frequency band at 22.74 cm –1 corresponds to molecular translation and the mid-frequency bands at 582.36, 1140.67, and 1299.72 cm –1 correspond to ring bending, twist, and rocking, CH 2 twist and rocking, and NN equatorial stretching and CH 2 rocking, respectively, as shown in Table S1 of the Supporting Information. The large change in scattering rates upon stimulating the low-frequency band can be attributed to a combination of two factors: (i) The lowest-frequency modes are responsible for over 99% of the mode-to-mode scattering (details can be found in our earlier work 61 ) due to their strong anharmonic coupling with other modes and a large phase space volume available for three-phonon scattering and (ii) the majority of the low-frequency modes scatter via absorption processes (ϕ 1 + ϕ 2 → ϕ 3 ) involving two other low-frequency modes, and since the increase in the phonon population of the stimulated low-frequency modes is ∼120%, a proportionate ∼29% increase is observed in the scattering rates. This increase in scattering rates also leads to a substantial decrease in average modewise diffusivity and scalar thermal conductivity by 15.58 and 12.46%, respectively, as shown in Figures 2 and 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“… 61 The details on the convergence of harmonic and anharmonic phonon properties with respect to the number of Brillouin zone sampling points can be found in the Supporting Information of our earlier work. 61 Based on the IR spectroscopy data in the literature, 97 104 15 IR active modes in RDX spanning the complete phonon spectrum are identified and shown in Table S1 . For each IR active mode, a band of discrete modes is defined using the spectral profile shown in Figure S1 .…”
Section: Computational Detailsmentioning
confidence: 99%